2019
DOI: 10.1016/s1875-5364(19)30021-4
|View full text |Cite
|
Sign up to set email alerts
|

Houttuynia cordata polysaccharide alleviated intestinal injury and modulated intestinal microbiota in H1N1 virus infected mice

Abstract: Houttuynia cordata polysaccharide (HCP) is extracted from Houttuynia cordata, a key traditional Chinese medicine. The study was to investigate the effects of HCP on intestinal barrier and microbiota in H1N1 virus infected mice. Mice were infected with H1N1 virus and orally administrated HCP at a dosage of 40 mgkg -1 d -1 . H1N1 infection caused pulmonary and intestinal injury and gut microbiota imbalance. HCP significantly suppressed the expression of hypoxia inducible factor-1α and decreased mucosubstances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…It has anti-inflammatory, anti-allergic, antioxidant and anticancer properties [ 62 ]. The bioactive compounds present in HCT are comprised of rutin, hyperin, isoquercitrin, quercetin, afzelin, reyoutrin, kalium sulfuricum, cordarine, decanoyl acetaldehyde, lauric aldehyde, myrcene, α-pinene, methyl nonyl ketone, d-limonene, linoleic acid, aspartic acid, palmitic acid, water-soluble polysaccharides, amino acids, vitamins, manganese, potassium, zinc, iron and copper [ 64 , 65 , 66 ]. During the SARS-CoV-1 infection, the leaves of this Chinese medicinal plant were used to treat patients and showed good efficacy against SARS-CoV-1 [ 48 , 57 ].…”
Section: Therapeutic Potential Of Medicinal Plants Against Sars-comentioning
confidence: 99%
“…It has anti-inflammatory, anti-allergic, antioxidant and anticancer properties [ 62 ]. The bioactive compounds present in HCT are comprised of rutin, hyperin, isoquercitrin, quercetin, afzelin, reyoutrin, kalium sulfuricum, cordarine, decanoyl acetaldehyde, lauric aldehyde, myrcene, α-pinene, methyl nonyl ketone, d-limonene, linoleic acid, aspartic acid, palmitic acid, water-soluble polysaccharides, amino acids, vitamins, manganese, potassium, zinc, iron and copper [ 64 , 65 , 66 ]. During the SARS-CoV-1 infection, the leaves of this Chinese medicinal plant were used to treat patients and showed good efficacy against SARS-CoV-1 [ 48 , 57 ].…”
Section: Therapeutic Potential Of Medicinal Plants Against Sars-comentioning
confidence: 99%
“…In addition, the recent application of TCMs in the treatment of novel coronavirus and influenza viruses has achieved good efficacy. Some studies have reported that the treatment of virus-related diseases with TCM may be related to the intestinal microecology, such as Houttuynia cordata can reverse the composition change of intestinal microbiota caused by H1N1 infection, with significantly reduced relative abundances of Vibrio and Bacillus, the pathogenic bacterial genera ( Chen et al., 2019 ). The latest researches have shown that the gut microbiota plays an important role in the progression of COVID-19, and that gut microbiota imbalance and endotoxemia may accelerate the progression of COVID-19 ( Gou et al., 2020 ).…”
Section: Interaction Mechanism Of Tcm and Intestinal Floramentioning
confidence: 99%
“…However, such barrier-enhancing activity lacks effective control. Moreover, the regulation of bacteria is also involved, and polysaccharides composed of Glc, Gal, Ara, and Rha at a 40 mg/kg dosage greatly reduced the relative abundance of the pathogenic bacteria Vibrio and Bacillus and alleviated the intestinal damage caused by H1N1 infection ( CHEN et al, 2019 ). These findings indicated that H. cordata polysaccharides and sodium houttuyfonate exert intestinal protective activity by regulating the intestinal flora and inhibiting the NF-κB signalling pathway to strengthen the intestinal barrier.…”
Section: Pharmacological Activitymentioning
confidence: 99%